Community-related Medical Education Classification: A Critical Review - Peigham Heidarpoor; Shahram Yazdani (Strides in Development of Medical Education)
Background: Community-related medical education has been defined under various terms, such as community-oriented medical education, community-based medical education, social accountability education, and community-engaged medical education. These terms have similar definitions and can be used interchangeably. The graduation of physicians who are familiar with the problems of the community is considered a necessity in modern medical education. As a result, numerous activities have been carried out worldwide, each given a different name.Objectives: This study intended to provide a more comprehensive classification of community-related medical education by examining the maximum number of educational programs and activities worldwide. The classification helps create a scientific and systematic view of this category and serves as a guide in planning and implementing such education.Methods: The present study is conducted using Carnwell and Daly's critical review method. The review was performed in different stages, including defining the review scope, identifying sources, reviewing, and constructing the texts. By reviewing documents and examining their similarities and differences, previous classifications are complete and updated.Results: Community-related medical schools are divided into socially responsible, socially responsive, and socially accountable schools, with medical curricula that are community-oriented, community-based, and community-engaged, respectively. All schools are subdivided into education, research, and service-oriented programs.Conclusion: Community-related educational programs can be designed and implemented at different levels according to the context.